Koordinasi Proteksi Relai Arus Lebih pada Sistem Distribusi Radial Menggunakan Jaringan Syaraf Tiruan Perambatan Balik - Frediansyah, Andy; Facta, Mochammad; Handoko, Susatyo (Universitas Semarang, 2022)
To reduce damage to electrical power equipment, protective equipment is needed that is designed as well as possible, so that the protection relay can isolate faults in parts of the distribution network as fast as possible. This backup protection need appropriate relay coordination, so that could protect, if it happens of a primary protection failure. To provide the best service to customers, it is necessary to coordinate the protection relay in the electric power system. To provide protection, the protection relay in the electric power system must be properly coordinated. In this study, we will make a simulation to calculate the TDS and Ipickup values of the overcurrent relay using a artificial neural network backpropagation with software Matlab R2016a. The results of this study can determine the value of TDS (Time Dial Setting) and Ipickup (Current pickup) by overcome the main problem of overcurrent relay protection coordination at the Ammurea II Factory PT. Petrokimia Gresik using a method artificial neural network backpropagation. And, also obtained the results of the minimum value of MSE (Mean Square Error) with the process using the method artificial neural network backpropagation.